2003
DOI: 10.1111/j.1939-1676.2003.tb02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Feline Epitheliotropic Intestinal Malignant Lymphoma: 10 Cases (1997–2000)

Abstract: The clinical, histopathologic, and immunohistochemical features of 10 cats with epitheliotropic intestinal malignant lymphoma (EIL) are described. Intestinal biopsy samples were reviewed by 3 pathologists to confirm the diagnosis of EIL. These samples (n = 10) were compared to the intestinal biopsies of normal cats (n = 11), cats with inflammatory bowel disease (IBD; n = 7), and cats with non-EIL (n = 9) for quantification and immunophenotyping of intraepithelial lymphocytes. Immunophenotypic studies were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(137 citation statements)
references
References 15 publications
11
125
0
1
Order By: Relevance
“…Those remission and survival times of cats with gastric lymphoma were comparable to those in previous reports of high-grade feline lymphoma. 16,[19][20][21][22][23][24] Although a chlorambucil and prednisolone protocol is not typically used in the treatment of high-grade lymphoma, the one cat receiving that protocol in this study did so due to owner prefer- This study supports the fact that future studies to investigate the benefit of surgery in treatment of feline gastric lymphoma and the hormonal impact on the risk and response to treatment in feline gastric lymphoma are warranted. Additionally, prospective studies to identify a more favorable chemotherapy protocol, either first-line or rescue, based on remission duration and associated toxicities are very much needed for this disease.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Those remission and survival times of cats with gastric lymphoma were comparable to those in previous reports of high-grade feline lymphoma. 16,[19][20][21][22][23][24] Although a chlorambucil and prednisolone protocol is not typically used in the treatment of high-grade lymphoma, the one cat receiving that protocol in this study did so due to owner prefer- This study supports the fact that future studies to investigate the benefit of surgery in treatment of feline gastric lymphoma and the hormonal impact on the risk and response to treatment in feline gastric lymphoma are warranted. Additionally, prospective studies to identify a more favorable chemotherapy protocol, either first-line or rescue, based on remission duration and associated toxicities are very much needed for this disease.…”
Section: Discussionmentioning
confidence: 56%
“…The median age of cats with gastric lymphoma was 12.8 yr, similar to previous reports of gastrointestinal lymphoma. 2,5,[21][22][23][24] Vomiting was the most common clinical sign reported in this study, in contrast to most reports of feline gastrointestinal lymphoma in which weight loss was more common. 2,19,21,23,24 Lymphoma of the gastrointestinal tract can present as either diffuse infiltration or a discrete mass.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Feline GI small cell T-cell lymphoma is becoming recognized as a distinct form of GI lymphoma in cats, 4,5,9,12,16 and appears similar to IBD on ultrasound and histology. Both IBD and lymphoma are characterized by diffuse or segmental distribution in the small intestine, with ultrasonographic features of bowel wall thickening owing to increase of the muscularis propria and preservation of wall layers without mass formation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Carreras et al reported on 10 cases of feline epitheliotropic intestinal lymphoma, all of which were described as consisting of small to intermediate-sized lymphocytes, and all stained positive for presence of the CD3 T-cell marker. 13 …”
Section: Discussionmentioning
confidence: 99%